2015
DOI: 10.3109/15360288.2015.1082010
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Pediatric Pain Management in Children Undergoing Surgery: A Survey of Health Care Providers

Abstract: The appropriate pain management in neonates and children is lacking. Factors that prevent the execution of proper pain relief vary from center to center. We studied the factors responsible for it in a surgical unit. We conducted a survey at a tertiary-level institute among the resident doctors and nursing staff by means of an informal questionnaire analyzing their basic knowledge. The questions pertained mainly to pain assessment, analgesic usage, role of opioids, and formal training, and the responses so obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…HCPs' correct answer rate to questions related to this group of patients was the lowest. Likewise other studies described the ill preparation of HCPs to assess and manage children's pain [15, 16, 27, 50, 54, 55]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCPs' correct answer rate to questions related to this group of patients was the lowest. Likewise other studies described the ill preparation of HCPs to assess and manage children's pain [15, 16, 27, 50, 54, 55]. …”
Section: Discussionmentioning
confidence: 99%
“…Mostly what they show was that in general many HCPs, especially nurses, lack adequate knowledge about pain, which led to undertreatment of pain [13, 1823]. Studies had also shown that HCPs bear misconceptions and myths about pain that impede proper pain management [22, 2427]. …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, studies have found that many pediatric clinicians focus on the source rather than the symptom (Gaglani, & Gross, 2018; Subhashini, Vatsa, & Lodha, 2009; Twycross, & Dowden, 2009), feeling that in the urgency of saving a life, there is no time to provide effective pain management (Mathews, 2011; Nimbalkar et al, 2014). Many studies have documented that knowledge deficits and negative attitudes of healthcare providers regarding pain management are the most important factors impacting pediatric pain relief care (Mathew et al, 2011; Nimbalkar et al, 2014; Stanley & Pollard, 2013), and that pediatric clinicians' knowledge and attitudes regarding pediatric pain management can affect their willingness to provide such care (Abdulaziz, 2017; Alotabi, Higgins, & Chan, 2019; Alotaibi, Higgins, Day, & Chan, 2018; Bawa, Mahajan, Aggerwal, Sundaram, & Rao, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, it has been unclear what factors impact pediatric pain management in Taiwan, some of which possibly result from a lack of education or professional experience. Additionally, there is a lack of credible research into the structural culture and perceptions of pediatric pain management among clinicians (Abdulaziz, 2017; Bawa et al, 2015; Finley, Kristjánsdóttir, & Forgeron, 2009). Thisstudyis in response to the scarcity of studies of the knowledge and attitudes of pediatric clinicians regarding pediatric pain management and the utter lack of investigation into the barriers to such care in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…This disparity is exacerbated in general EDs, which treat both adults and children in the same location [7]. Some identified barriers to optimal pain management include lack of or inaccurate pain assessments [810], hesitation regarding the use of opioids in children among prescribers [11, 12], and failure to include non-pharmacologic strategies in the treatment of pain. However, interventions targeting improved documentation of pain scores did not translate into improved analgesic treatments [13, 14].…”
Section: Articlementioning
confidence: 99%